HUBUNGAN TINGKAT PENGETAHUAN DENGAN PERILAKU IBU DALAM MENERAPKAN TOILET TRAINING PADA ANAK USIA TODDLER (3-5 TAHUN) - Ni Putu Kusuma Dewi; IGAA Sherlyna Prihandhani; I Made Dwie Pradnya Susila; I Nyoman Sutresna (Forind Press, 2026)
The high prevalence of toddlers who defecate and urinate indiscriminately is caused by delayed toilet training. Toilet training is an effort to train children to control their urination and defecation. The toilet training process requires attention to the mother's behavior. This behavior may be caused by the mother's level of knowledge about toilet training. This study aims to determine the relationship between mothers' knowledge and behavior in implementing toilet training for toddler-aged children (3-5 years) in Banjar Anyar Kelod Kerobokan. The study was conducted using a quantitative design with an analytical survey approach and a cross-sectional design, carried out from February to March 2025 with a sample size of 32 respondents selected using total sampling technique. Data were collected using a toilet training knowledge questionnaire and a mother's behavior questionnaire in implementing toilet training. Data were analyzed using the chi-square test with p<0.05. The results showed that most mothers had good knowledge about toilet training (68.8%) and most exhibited good behavior in implementing toilet training (65.6%). The analysis revealed a significant association between the level of knowledge and behavior of mothers in implementing toilet training for toddlers (3-5 years old) in Banjar Anyar Kelod Kerobokan, with a p-value <0.001. The recommendations of this study are expected to provide input for mothers in implementing toilet training for toddlers.